A162 SHIFT IN DISPARITIES IN HCV TREATMENT FROM INTERFERON TO DAA ERA: A POPULATION BASED COHORT STUDY. (1st March 2018) - Janjua, N Z; Islam, N; Wong, J; Yoshida, E M; Ramji, A; Samji, H; Butt, Z; Chong, M; Alvarez, M; Cook, D; Tyndall, M; Krajden, M
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CIHR